The Effectiveness of Behavioral Group Counseling with Self-Management and Token Economy Techniques to Reduce Academic Procrastination - Apriatmoko, Bayu Aji Dwi; Awalya, Awalya; Mulawarman, Mulawarman (Jurnal Bimbingan Konseling, 2022)
Academic procrastination has negative impact on the decline in students’ academic achievement. This study aimed to examine the effectiveness of behavioral group counseling with self-management and token economy techniques to reduce the academic procrastination of students at SMA Negeri 12 Semarang. It was an experimental study which used randomized pretest-posttest comparison group design and involved 14 grade eleven students chosen purposively of 429 people. The subjects were then grouped into two, namely one group received a self-management technique, and another one received a token economy technique for 4 sessions for each. Findings showed that both techniques were effective to reduce the academic procrastination of the students at SMA Negeri 12 Semarang, while each technique contributed equal impact. The interesting thing from the results of this study was that attention disorder became the most influential aspect in shaping academic procrastination in students.